Partial least squares – path modelling for efficiency assessment in the colombian professional football league (2022)
This research develops a production function to evaluate the teams’ efficiency in the Colombian professional soccer league. The designed methodology uses the concepts of structural equations and Data Envelope Analysis. In the development of the research, primary information associated with the sports and financial performance of the 20 Colombian Professional soccer teams was collected, with which a structural equation model was established that was empirically validated to evaluate the efficiency of each football team finally holistically. As result of this research, it can be pointed out that the proposed PLS structural model validates the hypotheses about the relationships between the latent variables. Similarly, the results show that the best Colombian soccer teams for the analyzed period are Medellín, Tolima, Nacional, and Junior.